Ankylosing Spondylitis and Posture Control: The Role of Visual Input. (3rd March 2015) - De Nunzio, Alessandro Marco; Iervolino, Salvatore; Zincarelli, Carmela; Di Gioia, Luisa; Rengo, Giuseppe; Multari, Vincenzo; Peluso, Rosario; Di Minno, Matteo Nicola Dario; Pappone, Nicola
Abstract : Objectives . To assess the motor control during quiet stance in patients with established ankylosing spondylitis (AS) and to evaluate the effect of visual input on the maintenance of a quiet posture. Methods . 12 male AS patients (mean age 50.1 ± 13.2 years) and 12 matched healthy subjects performed 2 sessions of 3 trials in quiet stance, with eyes open (EO) and with eyes closed (EC) on a baropodometric platform. The oscillation of the centre of feet pressure (CoP) was acquired. Indices of stability and balance control were assessed by the sway path (SP) of the CoP, the frequency bandwidth (FB1) that includes the 80% of the area under the amplitude spectrum, the mean amplitude of the peaks (MP) of the sway density curve (SDC), and the mean distance (MD) between 2 peaks of the SDC. Results . In severe AS patients, the MD between two peaks of the SDC and the SP of the center of feet pressure were significantly higher than controls during both EO and EC conditions. The MP was significantly reduced just on EC. Conclusions . Ankylosing spondylitis exerts negative effect on postural stability, not compensable by visual inputs. Our findings may be useful in the rehabilitative management of the increased risk of falling in AS.